2020
DOI: 10.1007/jhep06(2020)144
|View full text |Cite
|
Sign up to set email alerts
|

Classical gravitational scattering at $$ \mathcal{O} $$(G3) from Feynman diagrams

Abstract: We perform a Feynman diagram calculation of the two-loop scattering amplitude for gravitationally interacting massive particles in the classical limit. Conveniently, we are able to sidestep the most taxing diagrams by exploiting the test-particle limit in which the system is fully characterized by a particle propagating in a Schwarzschild spacetime. We assume a general choice of graviton field basis and gauge fixing that contains as a subset the well-known deDonder gauge and its various cousins. As a highly no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 98 publications
(156 reference statements)
2
75
0
Order By: Relevance
“…[19,20] in the case of Einstein gravity. Since then, the correctness of the latter result has been verified at high orders in the velocity expansion [48,49], an alternative method for resummation of the velocity series has been used with identical results [50], and the unitarity cut construction of the loop integrand has been checked against direct Feynman diagram computations [51]. Still, a direct relativistic calculation that bypasses velocity resummation will be a valuable additional confirmation of the result, and will provide a way to streamline future calculations at O(G 3 ) and beyond.…”
Section: Jhep11(2020)023mentioning
confidence: 99%
“…[19,20] in the case of Einstein gravity. Since then, the correctness of the latter result has been verified at high orders in the velocity expansion [48,49], an alternative method for resummation of the velocity series has been used with identical results [50], and the unitarity cut construction of the loop integrand has been checked against direct Feynman diagram computations [51]. Still, a direct relativistic calculation that bypasses velocity resummation will be a valuable additional confirmation of the result, and will provide a way to streamline future calculations at O(G 3 ) and beyond.…”
Section: Jhep11(2020)023mentioning
confidence: 99%
“…Transforming to impact parameter space b by means of a Fourier transform in D − 2 dimensions yields 20) while the same Fourier transform for the tree level amplitude (3.7) gives…”
Section: Eikonal Exponentiation and Unitaritymentioning
confidence: 99%
“…Given the expected improvements in detector sensitivity, it will be extremely important in the future to have high-precision theoretical predictions from General Relativity. To this aim the use of quantum field theory amplitudes to extract the post-Minkowskian (PM) expansion of General Relativity has recently gained considerable momentum [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], and progress is now also being made on extensions to spinning objects [22][23][24][25][26][27][28][29][30][31]. The underlying physical motivation for this approach lies in the observation that, during the early stages of a merger event, when the two compact objects are still far apart, gravitational interactions are weak and can be conveniently treated JHEP07(2020)122 in a weak-coupling approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews on this topic from different perspective can be found in [37][38][39][40]. In the post-Minkowskian framework, which is natural in the context of amplitudes, the current state of the art is at 3PM order [41,42], a result which was recently confirmed in [35,43]. Note also the effective one-body approach of [44], recently extended to incorporate the first and second post-Minkowskian corrections in [45,46], respectively.…”
Section: A Overviewmentioning
confidence: 97%